DESIGN AND DEVELOPMENT OF A WORDWALL-BASED ASSESSMENT GUIDED BY THE FIVES LEARNING MODEL TO FOSTER STUDENTS' CRITICAL THINKING SKILLS - Lutfiatuzzahroh; Sri Dewi Nirmala; Ryan Dwi Puspita (Universitas Majalengka, 2026)
The limited development of critical thinking skills among elementary school learners indicates the necessity of assessment innovations that extend beyond measuring academic achievement and actively promote higher-order thinking processes. This study was conducted to design a Wordwall-based digital assessment grounded in the FIVES instructional framework and to evaluate its validity, practicality, and effectiveness in enhancing the critical thinking performance of fifth-grade students at SD Dharma Karya UT. The investigation adopted a Research and Development approach employing the ADDIE framework, encompassing the phases of analysis, design, development, implementation, and evaluation. The participants consisted of 48 students assigned to experimental and control groups. Data were obtained through expert appraisal, questionnaires, classroom observations, interviews, documentation, and critical thinking assessments. The results revealed that the developed assessment attained a very high level of validity based on expert judgments and demonstrated excellent practicality from the perspectives of teachers and students. In terms of effectiveness, the average score of the experimental group rose from 55 before treatment to 84 after treatment, producing an N-Gain value of 0.64, whereas the control group achieved an N-Gain value of 0.53. Statistical analysis using a paired-samples t-test yielded a significance level of 0.000 (p < 0.05), confirming a significant improvement in students’ critical thinking abilities following the implementation of the developed assessment. Overall, the findings demonstrate that the developed assessment met the criteria of validity, practicality, and effectiveness, supporting its use as a digital assessment tool for enhancing fifth-grade students' critical thinking skills.